The effect of subjective norm and electronic word of mouth on university choice - Tirta Alkautsar Amril; Abror (Operations Management and Information System Studies, 2023)
The purpose of this study was to determine the effect of subjective norms and electronic word of mouth on university choice with brand equity as a mediating variable (case studies at Universitas Negeri Padang). This research is quantitative research with the positivistic method. The sampling technique in this study used the nonprobability sampling method, namely the purposive sampling technique. Data was collected using a questionnaire in the form of a Likert scale with five alternative answers. The data analysis technique used SEM-PLS with software SmartPLS version 3. The results of the study found that subjective norms had a direct and significant effect on university choice. E-wom has a direct and significant effect on university choice. Brand equity has a direct and significant effect on university choice. Subjective norms have a direct and significant effect on brand equity. E-wom has a direct and significant effect on brand equity. There is an influence of subjective norms on university choice mediated by brand equity. There is an influence of e-wom on university choice mediated by brand equity.